2008
DOI: 10.1177/0145482x0810200503
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Social Experiences of Students with Deaf-Blindness who are Educated in Inclusive Settings

Abstract: This qualitative case study investigated the nature of social experiences and opportunities for communication among students who are deaf-blind, their sighted peers with no hearing loss, and adults in inclusive settings. Strategies used by adults to promote interaction were also observed. Implications and suggestions for future research are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The analysis of the social validity outcomes in this study revealed that caregivers of individuals with CDB consider the HQC intervention to be a relevant intervention. The data show that caregivers in this study were very positive about receiving a communication intervention, which is in line with studies that report a need for communication support among caregivers of individuals with deafblindness (Janssen et al, 2003;Janssen et al, 2004;Correa-Torres, 2008). All the participants in our study rated the use of communication support for caregivers of deafblindness and the use of a communication coach as very good ideas on the Social Validity Scale.…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of the social validity outcomes in this study revealed that caregivers of individuals with CDB consider the HQC intervention to be a relevant intervention. The data show that caregivers in this study were very positive about receiving a communication intervention, which is in line with studies that report a need for communication support among caregivers of individuals with deafblindness (Janssen et al, 2003;Janssen et al, 2004;Correa-Torres, 2008). All the participants in our study rated the use of communication support for caregivers of deafblindness and the use of a communication coach as very good ideas on the Social Validity Scale.…”
Section: Discussionsupporting
confidence: 89%
“…Group 2: Studies reported that those with acquired deafblindness are more likely to experience constant social isolation in their lives due to the progressive impairments, ongoing loss of independence, and frequent worries (due to uncertainty about the process of the progressive loss and how to cope with it) [ 29 , 32 , 33 , 67 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clark (2005) advocates for combining these methods as appropriate into what she has termed the Mosaic approach. It is of note that many of these methods will not work with our youngest participants such as infants and toddlers, or children who are severally disabled (Correa-Torres, 2004). For example, 'the diary method may not be suitable for people [children] who can not write or have diffi culty articulating their feelings in writing' (Liamputtong, 2007: 154).…”
Section: Innovative Research Methodsmentioning
confidence: 99%